LEGAL EFFECTS ON CONTROL OF RIGHTS TO LAND OF THE FORMER EIGENDOM VERPONDING STATE IN DISPUTES BETWEEN HEIRS THE MULLER FAMILY WITH CITIZENS OF DAGO ELOS BANDUNG - Asnanda, Anggraeni; Rahmatiar, Yuniar; Abas, Muhamad; Sanjaya, Suyono (Awang Long Law Review, 2024)
Indonesia's Basic Agrarian Law (UUPA) sets out the requirements for the conversion of verponding eigendom land, regulating the rights of Westerners to be included in the applicable land law system. Based on the UUPA, land rights must be converted until September 24 1980. However, there are still frequent claims of land ownership resulting from eigendom disputes that have not been legally resolved, which causes land disputes. Case of verponding eigendom land dispute between the heirs of the Muller Family, PT. Dago Inti Graha versus Dago Elos residents is a clear example of the complexity that can occur in land ownership issues. Since it started in 2016, this dispute has been decided four times, one of which was at the PK level with Case Register Number 109 PK/Pdt/2022. Normative juridical and analytical descriptive approaches, in legal studies and relevant legal cases are analyzed. Result: According to the provisions of UUPA and its implementing regulations, as well as Government Regulation no. 24 of 1997, if there is no land eigendom verponding convention, the land then becomes state property. Through the trial, the Panel of Judges considered that the heirs of the Muller Family had succeeded in proving that they were the legal holders of land rights, compared to the claims of Dago Elos Residents who did not have proof of ownership and that the Muller Family heirs had more complete and valid supporting documents than the Residents. Dago Elos. Based on these considerations, the judge decided that the heirs of the Muller family had stronger and more legal rights to the disputed land than the Dago Elos residents. Therefore, the legal consequences for control of disputed land are that the heirs of the Muller family have the right to register the land and obtain legal recognition of ownership of the disputed land.